(untitled) (Baghdad Science Journal, 2025)
Fever is a common illness in the pediatric age group ,the causes could be viral ,bacterial and fungal , this study was focused on bacterial pathogens as gram positive like Staphylococci, coagulase positive or negative ,Streptococci and gram negative like E-coli , Klebsialla ,Proteus, Pseudomonas, Burkhoderia , Acinetobacter and others like Pusturella ,E-alkalescendiaper, Haemophillus influenza and yeast like candida . Four thousand and seventy eight blood samples (4078)were collected in a period between January 2011 and the end of May 2012 at the child welfare hospital ,all the samples were cultured on suitable culture media and then biochemical tests were done using API-E 20 and sugar fermentation tests ,sensitivity test were done with number of antibiotics [1]. 4078 cases examined only ,1107 showed positive growth ,264cases were contaminated and no bacterial growth seen in 2707. The bacterial isolates during one year in pediatric age groups were mostly gram positive cocci ,followed by gram negative bacilli,and yeasts .